Using Implementation Science to Assess Barriers to Agreement on Sedation Goal Setting and Assessment - Yang, Youyang; Becla, Kate; Kennedy, Heather; Eder, Katrina; Akhondi-Asl, Alireza; Mehta, Nilesh M; Geva, Alon (Pediatric critical care medicine, 2025)
Sedation assessment and goal setting using a validated assessment tool are key components of the ICU Liberation bundle. Appropriate integration of these bundle elements into daily practice remains challenging. Understanding barriers is an important step toward implementation of these best practice bundle elements. Two-phased explanatory mixed methods assessment carried out 2022-2023. Forty-bed quaternary PICU. Bedside nurses and prescribers caring for mechanically ventilated patients on sedative infusions. None. Forty-one nurses and 32 prescribers participated in the phase 1 pre-education assessments (2022). We identified lack of correlation between the providers' stated State Behavioral Scale (SBS) numerical goal and descriptive goal and hypothesized that this discrepancy was either due to a knowledge gap or disagreement on sedation goals. To investigate this hypothesis, we performed a phase 2 assessment (2022-2023), starting with a multipronged educational activity, followed by a repeat survey that included a qualitative interview. One hundred ninety nurses and 45 prescribers received the educational activity. Twenty-eight nurses and 22 prescribers participated in the phase 2 assessments with the qualitative interview. Although correlation of the sedation goal between providers improved, it remained poor. Subsequent qualitative interview data indicated that the reasons for persistent disagreement in the sedation goal for a given patient were related to individual providers' beliefs and attitudes toward sedation, rather than lack of understanding about using the SBS to set a target sedation goal. Barriers to setting and managing daily patient sedation goal in the PICU extend beyond providers' knowledge gaps. An improved understanding of underlying barriers is essential for successful implementation of evidence-based sedation guidelines.